1987
DOI: 10.1136/bjo.71.9.676
|View full text |Cite
|
Sign up to set email alerts
|

'Blow-outs' in the retinal pigment epithelium.

Abstract: SUMMARY A hole was detected in the epithelium of a retinal pigment epithelium (RPE) detachment in two patients. Leakage through the hole led to an elevation of the overlying neurosensory retina in each case. The resulting vision was 20/70 in one eye and 20/30 in the other. The defects in the RPE occurred in a setting different from that usually seen with tears in the pigment epithelium and had a different clinical appearance.Two patients were seen who had a defect in the epithelium of a retinal pigment epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 10 publications
2
31
1
1
Order By: Relevance
“…15 It has been postulated in the past that mechanical stress in CSC may cause RPE to give way at some point, which is observed as a point of leak on fluorescein angiography. 4,6 The breach will allow the passage of fluid, including particulate matter, into the subretinal space from the underlying hyperemic choroid. This would also mean that the resolution of subretinal fluid could result from decreased effusion from choroid, accompanied by a healing of the RPE microrip.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 It has been postulated in the past that mechanical stress in CSC may cause RPE to give way at some point, which is observed as a point of leak on fluorescein angiography. 4,6 The breach will allow the passage of fluid, including particulate matter, into the subretinal space from the underlying hyperemic choroid. This would also mean that the resolution of subretinal fluid could result from decreased effusion from choroid, accompanied by a healing of the RPE microrip.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a microrip or 'blow-out' in this PED has been postulated to result in a focal leak, which is observed as the point of leak on fluorescein angiogram. [4][5][6] Recently, a RPE defect within the PED at the leakage site has been reported on both time-domain 7 and fourier-domain OCT. 8 Fujimoto et al 8 observed RPE abnormalities at the site of leakage in 96% of eyes, with 22% of the eyes showing an RPE defect that was successfully treated with thermal laser photocoagulation. However, the natural course of these RPE abnormalities observed in the acute phase of CSC is not known.…”
mentioning
confidence: 99%
“…The choroid is thickened, and the resultant increase in choroidal hydrostatic pressure is thought to perhaps overwhelm the RPE and result in the accumulation of SRF and PEDs. 3,5,6 The pathophysiologic role of corticosteroids in the exacerbation of CSCR may be via their action on the RPE, Bruch's membrane, or the choroid, but the exact mechanism remains unclear and requires further study. 2,[7][8][9] There are multiple reports describing the association between exogenous corticosteroid and CSCR.…”
Section: Discussionmentioning
confidence: 99%
“…62 Goldstein and Pavan noted "blowouts of the RPE" at the dome of the PED without any retraction or rolling of the torn RPE layer. 28 In one case the site which showed tremendous leakage of dye into the subretinal space on FFA, was later noted to develop a RPE defect. Hence, they suggested that the intense leakage across the RPE in CSC can lead to weakening and eventual disintegration of these cells, causing 'RPE blow-out'.…”
Section: Figure 4: Blowouts Of Rpe In Csc (A) Fundus Photo Shows a Lmentioning
confidence: 99%
“…Rpe Tears In Central Serous Chorioretinopathy -"Blow-outs of the RPE" Goldstien and Pavan 28 described two patients with defects in the RPE underlying a neurosensory elevation. Both their cases occurred in middle aged men in the setting of severe CSC.…”
mentioning
confidence: 99%